Compliance in clinical trials. Issue 10 (October 1989) - Pullar, T; Kumar, S; Feely, M
Abstract : Compliance with treatment can be an important determinant of the outcome of clinical trials. To date there is no completely satisfactory method of measuring compliance and some of the most widely used methods are inadequate. The various methods of measuring compliance and how they have been applied to clinical trials are described, and improvements in the standard of the measurement and reporting of compliance in clinical trials are suggested.